2007
DOI: 10.1128/jb.01294-06
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Screening of Genes Required for Swarming Motility inEscherichia coliK-12

Abstract: Escherichia coli K-12 has the ability to migrate on semisolid media by means of swarming motility. A systematic and comprehensive collection of gene-disrupted E. coli K-12 mutants (the Keio collection) was used to identify the genes involved in the swarming motility of this bacterium. Of the 3,985 nonessential gene mutants, 294 were found to exhibit a strongly repressed-swarming phenotype. Further, 216 of the 294 mutants displayed no significant defects in swimming motility; therefore, the 216 genes were consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
169
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(193 citation statements)
references
References 51 publications
14
169
1
9
Order By: Relevance
“…An anti-type 1 pili monoclonal antibody partially blocked motility of the UPEC bacteria, presumably because of steric hindrance as the result of the antibody attaching to the type 1 pili and impeding the action of the bacterial flagella. Alternatively, recent data suggests that type 1 pili may provide a supporting function in swarming motility (Inoue et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…An anti-type 1 pili monoclonal antibody partially blocked motility of the UPEC bacteria, presumably because of steric hindrance as the result of the antibody attaching to the type 1 pili and impeding the action of the bacterial flagella. Alternatively, recent data suggests that type 1 pili may provide a supporting function in swarming motility (Inoue et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In another previous report (28), the surface motility of JW1908 (ME9062 except ⌬fliC) was abolished. Accordingly, we confirmed that JW1908 exhibits a defect in surface motility.…”
Section: Surface Motility Observed In the Presentmentioning
confidence: 99%
“…YeeF has recently been annotated as a putrescine importer in several databases. In addition, the ⌬yeeF mutant was listed in 294-single gene knock-out mutants that exhibited a repressed-swarming phenotype selected in a genome-wide screening (28). Yet, its function was not reported.…”
Section: Genome-wide Gene Expression Comparison Between Strains That mentioning
confidence: 99%
“…Interestingly, a recent survey of gene differences in B. anthracis and B. cereus using suppression subtractive hybridization and bioinformatic analysis of Bacillus whole genome sequences found a glycosyltransferase group 1 family gene apparently specific to B. anthracis (26). Although the involvement of this gene in HF-PS biosynthesis is, at this point, not clear and currently under investigation in our laboratory, it is worth mentioning that from the few currently characterized bacterial galactosyltransferases some belong to the group family 1 glycosyltransferases (11,27). Moreover, since all of the HF-PSs contain ManNAc, mutation of genes that encode for ManNAc biosynthetic proteins should prevent the synthesis of the HF-PS and allow evaluation of functional importance (i.e.…”
mentioning
confidence: 99%